Spontaneous and photosensitiser-induced DNA single-strand breaks and formamidopyrimidine-DNA glycosylase sensitive sites at nucleotide resolutionin the nuclear and mitochondrial DNA of Saccharomyces cerevisiae. - Meniel, V (1999)
A system is described for mapping oxidative DNA damage (sites sensitive to formamidopyrimidine-DNA glycosylase and single-strand breaks) at nucleotide resolution in the nuclear and mitochondrial DNA of Saccharomyces cerevisiae. Our 3' end labelling method is sensitive and was first developed using the well-studied inducer of oxidative DNA damage, methylene blue (MB) plus light. We treated yeast DNA in vitro with this so as to maximise levels of damage for assay development. Unfortunately, MB does not remain in yeast cells and yeast DNA repair mutants sensitive to active oxygen species are not sensitive to this agent, thus for in vivo experiments we turned to a polycyclic aromatic, RO 19-8022 (RO). This resulted in oxidative DNA damage when light was applied to yeast cells in its presence. The spectra of enzyme-sensitive sites and single-strand breaks induced by MB in vitro or by RO plus light in vivo or in vitro were examined in two yeast reporter genes: the nuclear MFA2 and the mitochondrial OLI1. The experiments revealed that most of the enzyme-sensitive sites and single-strand breaks induced by MB or RO plus light are at the same positions in these sequences, and that these are guanines.